Pulmonary Alveolar Type II Cells Isolated from Rats: RELEASE OF PHOSPHATIDYLCHOLINE IN RESPONSE TO β-ADRENERGIC STIMULATION - Dobbs, Leland G. (1979)
It is unclear what factors control the secretion of pulmonary surface active material from alveolar type II cells in vivo. Other workers have suggested that cholinergic stimuli, adrenergic stimuli, and prostaglandins may all stimulate secretion. We isolated type II cells from the lungs of rats by treatment with elastase, discontinuous density centrifugation, and adherence in primary culture. β-Adrenergic agonists, but not cholinergic agonists, caused an increase in the release of [(14)C]disaturated phosphatidylcholine, the major component of surface-active material, from type II cells in culture. The β-adrenergic effect was stereo-selective, (−)-isoproterenol being 50 times more potent than (+)-isoproterenol. Terbutaline, 10 μM, a noncatecholamine β-2 adrenergic agonist, caused a release of 2.0±0.5 (mean±SD) times the basal release of [(14)C]disaturated phosphatidylcholine in 3 h; the concentration of terbutaline causing half maximal stimulation was 800 nM. The terbutaline effect was blocked by propranolol, a β-adrenergic antagonist (calculated K(d) = 6 nM), but not by phentolamine, an α-adrenergic antagonist. Isobutylmethylxanthine, a phosphodiesterase inhibitor, and 8-Br cyclic AMP, but not 8-Br cyclic guanosine monophosphate, also stimulated release. We conclude that type II cells secrete disaturated phosphatidylcholine in response to treatment with adrenergic stimulation.